A Review on Transdisciplinary Approach and Challenges on Wearable Technology - D. Bhuvana Suganthi; M. K. Vidhyalakshmi; A. Punitha; S. Raghupathi; M. Subhapradha (Recent Progress in Science and Technology Vol. 7, 2023)
Wearable Technology is an emerging technology that impacts in our daily life as a major part. This wearable technology become attractive due to its size, speed, storage, sensing behavior, and multifunctional capability. All wearable devices must have sensing capabilities. This paper focuses on various reviews, features, and applications of wearable technologies and is highlighted with basic ideas on the major technology. This paper helps the researchers who are beginners in this wearable technology. This platform keeps us more convenient and comfortable by trusting in its various capabilities. It gives a summary of the interaction between humans and technology. It deals with big data states that can able to handle huge amounts of information at a very high speed which can be able to process over time which creates perfect value and communicates to humans on time. Wearable technology plays a critical role as the heart of the system to deliver the data transformation. It is a type of gadget that makes our life easier by keeping us fit, flexible, and worldwide updates on time. This survey is towards the various instruments on wearable, their challenges, and research in the future.